ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK PENDIDIKAN SEKS OLEH IBU YANG MEMILIKI ANAK AUTIS USIA REMAJA (Studi di SLB Negeri Kota Semarang) - Yulia Ratih (Jurnal Kesehatan Masyarakat (Undip), 2016)
Adolescents with autism have resistance in controlled abstract concept, social interaction and behavior.Various problems appear when an autistic child becomes a teenager. Hygiene behavior, public and private, and sexual needs are examples of their problems. Sex education role in the teaching of norms of sexual behavior in adolescents with autism and independence in self-preservation.The role of mothers in giving the sex education is an effort to control the problem in adolescents with autism.The purpose of this research was to analyze the factors related to the practice of sex education by the mother in adolescents with autism in the SLB Negeri Semarang. The research population is the mother of an autistic students aged 6-24 years of some 55 people. The research sample taken some 48 people as the inclusion criteria.Results of respondents who obtained 34 people as there are seven respondents who are not willing and children who have been inactive school. Analysis of data using statistical analysis Chi Square test (significance level = 0.05). The result of research that, the majority of respondents aged ≥ 43 years (94.1%), the education level of respondents is advanced education (Senior High School until college) (91.2%), the income of respondents mostly ≥ IDR1,685 (82.4%), the job status of respondents was not working (76.5%). Variables related to the practice of sex education by the mother is income respondents (p = 0,048). Suggestion research are a parent provides facilities such as as the facilities and infrastructure support in the provision of sex education, the learning tools in supporting the interests and talents and give information about menstruation, masturbation, and parts of body.